If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3b+18=2b-4
We move all terms to the left:
3b+18-(2b-4)=0
We get rid of parentheses
3b-2b+4+18=0
We add all the numbers together, and all the variables
b+22=0
We move all terms containing b to the left, all other terms to the right
b=-22
| 4.8=3.2/t | | 10−u=85 | | 3y-18=2y-12 | | 12(2x+3)/5=48(x−1)/15 | | 4. -2x+2=3x-3 | | 3b+21=2b+8 | | 4(x−1)3=2x+1 | | 5x+5-2x=2x-5 | | 3a+18=2a+10 | | 4(x−1)/3=2x+1 | | -7x+6=2x-21 | | 16(p+24)= | | 3a+21=2a-2 | | 3=34(b-8) | | (x+2)/4+99=110 | | (x+2)4+99=110 | | 4(3x-4)=687 | | 3x-6=8x+8 | | -12m+40+42m+36=-74 | | 2x²–4x–70=0 | | 4t^2+12t=17 | | -12m+40+42m+36=-76 | | 7-4f=-13 | | X+7-8x/3=17/6+5x/2 | | X+7-8x/3=17/6 | | 4(2x+3)=−3(x−1)+31 | | 20-x/15=18 | | 1+5x/4=11 | | -3-2x=2-x | | -21x+26x=5 | | -38x+41x=21 | | 14=8x²+1 |